Cosmeceutical values, antimicrobial activities and antioxidant properties of cashew leaves extract - Chermahini, Siavash Hosseinpour (Academic Journals, 2011)
With the increasing concern of public health and consumers’ awareness, non-chemical cosmetics are booming worldwide. Plants are important in formulating natural and non-chemical cosmetic products, thus making the plant materials highly potential to be developed into cosmetic formulating ingredients. However, colour interference is a very critical item in producing cosmetic. The plant extracts which are normally dark brown and greenish colour, might spoil the appearance of the products if they are added in cosmetic formulation. In order to solve this problem, an activated carbon granule tea bag system was assembled and batch experiments were conducted as a mechanism to eliminate the intense colour of plant extract without affecting activities. The system was tested with different concentration of cashew leaves extract (5, 10, 15, 20, 25 and 30%) in contact with (10, 15, 20 and 25 g) granular activated carbon (GAC) from 0 to 6 h. Ethanol and water extracts of cashew leaves were compared for the cosmeceutical properties, mainly the antioxidant and antimicrobial activities. This study therefore suggests that cashew leaf extract is suitable to be used with ethanol for cosmetic application.